Calcium-Sensing Receptor Mediates β-Amyloid-Induced Synaptic Formation Impairment and Cognitive Deficits via Regulation of Cytosolic Phospholipase A2/Prostaglandin E2 Metabolic Pathway - Feng, Chenxi; Bao, Xiaoming; Shan, Ling; Ling, Yunxiang; Ding, Yanfei; Wang, Jia; Cao, Yanzi; Wang, Qinwen; Cui, Wei; Xu, Shujun (Frontiers in Aging Neuroscience, 2020)
Calcium-sensing receptor (CaSR) is a G protein-coupled receptor (GPCRs). Soluble β-amyloid peptide (Aβ) is one of the orthosteric modulators of CaSR, while, the role and underlying mechanism of CaSR in cognitive decline in Alzheimer’s disease (AD) is unclear. In this study, molecular technology such as live-cell imaging combined with behavioral tests were used to explore the role and the underlying mechanism of CaSR in the cognitive deficits in AD mice. The expression levels of CaSR were increased both in AD mice and Aβ1–42 (β-amyloid protein)-treated primary cultured neurons. Pharmacological inhibition of CaSR ameliorated recognitive and spatial memory deficits of Aβ1–42-oligomer-treated mice in a dose-dependent manner. Pharmacological inhibition of CaSR or down-regulation of the expression of CaSR by CaSR-shRNA-lentivirus prevented the impairment of filopodia, and the synapse induced by oligomeric Aβ1–42. The contents of cytosolic phospholipase A2 (cPLA2) and prostaglandin E2 (PGE2) in hippocampal neurons and tissue were increased after treatment with Aβ1–42 oligomers. Inhibition or down-regulation of CaSR mediates Aβ-induced synapse formation and cognitive deficits partially, through the activation of the cPLA2/PGE2 pathway. This study provides novel insights on CaSR, which is a promising therapeutic target for AD.